Leveraging educational quality in Southern African educational systems : a practitioners' perspective - Mawere, Munyaradzi; Rambe, Patient (Langaa Research & Pub. CIG, 2013)
In the early decades of the twenty-first century, erosion in the quality and effectiveness of education systems - especially in sub-Saharan Africa - has been compounded by factors such as exogenous pressures precipitated by unsystematic provision of foreign aid - fostering corrupt practices, inadequate teacher training, and limited deployment of professional educators to under-served communities. Yet, quality education is needed to attain high levels of critical thinking, analytic interpretation, academic creativity, innovativeness, effectiveness, and personal and inter-personal skills in problem solving. This book, which focuses on Mozambique, South Africa, Zambia and Zimbabwe, critically reflects on primary, secondary, and tertiary education in Southern Africa with a view to explore the opportunities, constraints, and challenges that practitioners, learners, and other educational stakeholders face in their daily lives. The book draws on the findings from the aforementioned countries, to advance the thesis that education in sub-Saharan Africa faces problems of epic proportions that require urgent attention. Hence, the primary objective of this book is to serve as a drive and medium for informed change, critical thinking, constructive analysis, and synthesis and evaluation of different situations, settings, and problems situated in the interface of theory and practice in the education fraternity.